PERANCANGAN SISTEM INFORMASI E-INVENTARIS BARANG PADA PUSAT REHABILITASI NARKOBA AR RAHMAN - Nasrullah; Fenny Purwani (JURNAL FASILKOM, 2022)
Currently the use of technology in the dissemination of information is very important for organizations or agencies. An information system is currently very supportive of activities for organizations or agencies which will then be reprocessed to be more useful for users of the information system itself. The Ar-Rahman Drug Rehabilitation Center itself is a rehabilitation center for drug addicts. To support their work, the staff at the Ar-Rahman Drug Rehabilitation Center are currently using the facilities available there. One of them is recording inventory of goods. Currently, the recording is still done manually, namely by recording what items are purchased and borrowed. From these causes, it is urgently needed to build an E-Inventory Information System Design at the Ar Rahman Drug Rehabilitation Center which functions to record any assets that are already owned that were previously recorded manually in the future to be digital. In the design it will use dfd and erd while the database uses waterfall. The expected results are an inventory system design that will be implemented in . Ar-Rahman Drug Rehabilitation Center and can be used as a basis for developers to create an inventory system. Ar-Rahman Drug Rehabilitation Center.